KASUS “SI PENENDANG SESAJEN” SEBAGAI REFLEKSI PEMBELAJARAN GUNA MENJAGA MUTU EKSISTENSI MODERASI BERAGAMA DI INDONESIA - I Dewa Gede Darma Permana dewa_permana21 (Jurnal Penjaminan Mutu, 2022)
Abstract Indonesia is a unique country, where differences and diversity can coexist within the framework of unity. However, diversity in Indonesia, especially in terms of belief, can also trigger disharmony conflicts in the form of cases of blasphemy. The case of Hadfana Fairus "The Kicker of Sesajen" is one example. Through a viral video circulating on social media, it shows him throwing and kicking offerings on Mount Semeru, Lumajang, East Java. Reflecting on these problems, the researcher is interested in studying more deeply about the implications of the case of "The Kicker of Sesajen" as a reflection of learning in order to maintain the quality of the existence of religious moderation. In this study, several formulations of the problem were formulated, namely related to the chronology of the case of "The Kicker of Sesajen", the urgency of religious moderation in Indonesia, and the last reflection of learning in the case of "The Kicker of Sesajen". Using this type of qualitative research with a case study approach, followed by the method of collecting data from literature or literature studies, as well as Miles and Huberman's interactive data analysis techniques, the results of this study indicate that religious moderation is quite urgent in a plural and multicultural Indonesia. On this basis, the case of "The Kicker of Sesajen" can provide a reflection of learning for religious people in maintaining the quality of the existence of religious moderation in Indonesia, both in terms of humanism, religiosity, and also the law. Keywords: The Kicker of Sesajen, Existence, Religious Moderation